Does money strengthen our social ties? Longitudinal evidence of lottery winners - Costa-Font, Joan (2023)
We study the effect of lottery wins on the strength of social ties and its different types, including support networks, in the United Kingdom. On average, we find that winning more in the lottery increases the probability of meeting friends on most days, which is consistent with the complementary effect of income on the strength of social ties. The opposite is true with regards to social ties held for more instrumental reasons such as talking to neighbours. Winning more in the lottery also lessens an individual support network consistently with a substitution of income and support network. However, further robustness checks reveal that such average lottery effects are driven by individuals exhibiting very large wins only, thus suggesting that small to medium-sized wins (below £10k) may not be enough to change people’s social ties and support network in a substantial way.